Kinematics and Dynamics Analysis of Human Jumping Mechanism - Qing Di; Cao Jujiang (Jixie chuandong)
Based on the analysis of physiological structure and jumping movement characteristics of human lower limb,the jumping model of the lower limb is simplified as a plane multi-rigid body motion system. According to the forward kinetics analysis,the position,velocity and acceleration models of joints,centroids of each component are established. On the basis of the kinematics analysis,the dynamics analysis is carried out by using the Lagrange method,the dynamics equations of the relation between force and position in the jumping phase are obtained,the theoretical foundation for the design of various humanoid jumping mechanisms is provided. Finally,by using workbench,the statics analysis of the foot components in different phases is carried out,and the deformation and stress distribution of the sole are obtained.